How Does English Language Learning Contribute to Social Mobility of Language Learners? - Imam Munandar (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
A part from educational purposes, the learning of English worldwide has been found to have social and economic implication to its learners. It is seen as â€œsocial and economical mobilizerâ€. In many countries, English learners are seen as more educated and thus gain some degree of higher respectability in their society. English is desired, even required by companies in recruiting their employees. Those who know English are easier in getting desirable jobs compared to non-English knower. Learning English becomes a tool to socially move to upper level. This certainly has significant implication to Teaching English as Second or Foreign language. Many countries become well aware of this phenomenon and thus rule out English become a must-taught subject in schools.Keywords: Sociolinguistics, English language learning, social mobility, English language curriculum.Copyright Â© 2015 by Al-Ta'lim All right reserved